MXene/cellulose nanocrystal-coated cotton fabric electrodes for wearable electronics - Duygun, İnal Kaan; Çelik Bedeloğlu, Ayşe (Springer Science and Business Media Deutschland GmbH, 2024)
Increasing mechanical properties without losing electrical properties is of great importance for the development of advanced electronic textile products and their use in different areas. In this study, a cost-effective and facile preparation of MXene/cellulose nanocrystal-coated cotton fabrics by drop-casting was carried out to investigate electrical and mechanical properties of plain woven cotton fabrics. MXene (Ti3C2Tx) and cellulose nanocrystal dispersions of MXene (5 wt.%, 10 wt.% and 15 wt.% cellulose nanocrystal content) were applied to cotton fabrics, and the coated fabrics were characterized in terms of their morphological and structural properties for their suitability for wearable electronics. The surface resistivity and mechanical properties were also determined to evaluate the effectiveness of coating. Ti3C2Tx/cellulose nanocrystal dispersions are suitable to obtain a low electrical resistivity (186.4 ?/sq) in cotton fabrics. The results also showed that increasing cellulose nanocrystal content results in a more stable coating layer on the cotton fabric and a high tensile (63.2 MPa) and elongation at break values are obtained (30.2%) as a result of that. © King Abdulaziz City for Science and Technology 2024.
Keywords: Cellulose nanocrystal; Electrical properties; Flexible electrodes; Mechanical properties; MXene; Wearable electronics